More than meets the eye. Issue 2 (7th February 2019) - White-Gibson, Ailbhe; Lennon, Paul; O'Regan, Esther; Timon, Conrad
Abstract : We report an extremely rare case of a hybrid tumour of the maxillary sinus. A 51-year-old man presented with a 6-week history of nasal congestion and epiphora. Radiological imaging demonstrated a maxillary sinus tumour, with extensive local invasion. Surgical excision included maxillectomy, left eye exenteration and free flap closure. Histology of the excised specimen showed a rare hybrid tumour containing adenoid cystic carcinoma, salivary duct carcinoma, epithelial-myoepithelial carcinoma and basal cell adenoma. Hybrid tumours are very rare tumour entities which are composed of at least two distinct tumour types. Each tumour entity conforms with a defined tumour type. The tumour entities of a hybrid tumour are not separated but have an identical origin within a definite topographical area. Diagnosis and appropriate management requires high index of suspicion, pathological endeavour to look for a more aggressive accompanying tumour and adequate oncological treatment according to the highest grade of tumour.